Suspected and Confirmed Acute Appendicitis During the COVID-19 Pandemic: First and Second Quarantines—a Prospective Study - Petrauskas, Vidas; Poskus, Eligijus; Luksaite – Lukste, Raminta; Kryzauskas, Marius; Petrulionis, Marius; Strupas, Kestutis; Poskus, Tomas (Frontiers in Surgery, 2022)
Purpose: COVID-19 posed an unprecedented modern global healthcare crisis affecting both elective and urgent surgery. The aim of this study is to evaluate the difference in presentation of acute appendicitis (AA) before and during COVID-19 era, the first and second quarantine. Methods: We performed a prospective study from December, 2018 to May, 2021 . Two cohorts were analysed - one with patients who presented to emergency department (ED) with suspected AA and the second - with confirmed AA. Both cohorts were divided to four groups: before COVID-19, during Ist quarantine, between Ist and IInd quarantine, during IInd quarantine. Data, such as demographics, time to first contact with health care provider and time to operation, laboratory tests, clinical stage of AA, length of stay and COVID-19 status were collected. 469 patients were enrolled. Results: 209 patients were male (45 %), 260 - female (55 %), median age - 33 years (24-45). In the first cohort of suspected AA there was no difference in sex, however more older patients presented to ED during first quarantine (41 years) vs other groups (28,5, 36, 32,5 years), p <0,000. Before the pandemic there was shorter duration of symptoms to first contact with health care provider (13 hours) vs other groups, p =0,001. In the second cohort of confirmed AA there was a shorter period of time to operation from first symptoms before the pandemic (22 hours) vs other groups (30, 35, 30,5 hour), p < 0.000. There were more complicated gangrenous, perforated appendicitis or periappendicular abscess in Group2 and 3(26, 22, 10 % and 26, 22, 2 % respectively) vs Group1 (20, 4, 3 %) and Group4 (22, 12, 2 %), p = 0.009. Hospital stay was longer during Ist quarantine (3 days) vs other groups (2 days), p = 0.009. Six patients were COVID-19 positive: one from Group3 and five from Group4 (p >0,05). Conclusions: Our study suggests that during the Ist quarantine of COVID-19 pandemic there was delayed presentation to ED with suspected AA and there were was a greater proportion of complicated appendicitis and longer hospitalization in confirmed cases as well.